ANTHROPOGENIC FORCES AND THE DEPLETION OF WETLANDS AROUND LAKE RUKWA IN SUMBAWANGA DISTRICT, TANZANIA - GWALEMA, SUSAN. R.; M. MALATA, CHUNGUEN. (IJRDO-Journal of Agriculture and Research (ISSN: 2455-7668), 2018)
The study set to assess how anthropogenic forces contributed to the degradation of wetlands around Lake Rukwa in Sumbawanga district, thereby depleting the lake and its resources. Specifically, it assessed how the human activities deplete the wetlands of Lake Rukwa; examined the human influence on the changes in depth and width of Lake Rukwa overtime and evaluated the awareness of people about the impacts of their activities on wetlands of lake Rukwa. Data were collected from randomly selected samples from the clusters of crop cultivators, pastoralists, fishermen, ward leaders and natural resource managers of Sumbawanga district. Methods of data collection included: interview, observation, physical measurement, documentation and administration of the questionnaire. Confirmatory Data Analysis (CDA) was used to link the relationship between human forces and the depletion of Lake Rukwa wetlands and to draw a conclusion. Findings revealed that, there was a big link between the depletion of Lake Rukwa wetlands, the shrinkage of the lake and the anthropogenic forces taking place around the lake. The study recommended that land users and stewards of Lake Rukwa in Sumbawanga district, be educated on the impacts of their economic activities on the lake resources and how to exploit them sustainably.